Pemilihan Strategi Penjualan Obat Apotik Antar Menggunakan Algoritma A Priori - Yahdi Kusnadi; Muhamad Auliya Ahsan (Universitas Mohammad Husni Thamrin, 2020)
Business competitors are required to think of a sales strategy to attract the attention of buyers, especially the amount of business competition that can increase sales. There are many ways used by a company to boost sales, even similar ways have been followed by other companies as competitors. Business competitors, especially Inter Pharmacies, are required to think creatively to increase sales. Using a sales database and assisted with algorithm A Priori data mining companies will know the pattern of selling goods and can determine the determination of the provision of goods and the right stock addition.